(untitled) (Clinics, 2023)
Objective: The authors investigated changes in vascular reactivity in rats following pilocarpine-induced status epilepticus. Method: Male Wistar rats weighing between 250g and 300g were used. Status epilepticus was induced using 385 mg/kg i.p. pilocarpine. After 40 days the thoracic aorta was dissected and divided into 4 mm rings and the vascular smooth muscle reactivity to phenylephrine was evaluated. Results: Epilepsy decreased the contractile responses of the aortic rings to phenylephrine (0.1 nM–300 mM). To investigate if this reduction was induced by increasing NO production with/or hydrogen peroxide L-NAME and Catalase were used. L-NAME (N-nitro-L arginine methyl ester) increased vascular reactivity but the contractile response to phenylephrine increased in the epileptic group. Catalase administration decreased the contractile responses only in the rings of rats with epilepsy. Conclusions: Our findings demonstrated for the first time that epilepsy is capable of causing a reduction of vascular reactivity in rat aortas. These results suggest that vascular reactivity reduction is associated with increased production of Nitric Oxide (NO) as an organic attempt to avoid hypertension produced by excessive sympathetic activation.